(untitled) (Jurnal Pendidikan Fisika, 2026)
The development of students’ scientific attitudes remains a major concern in physics education, as classroom instruction still tends to prioritize cognitive achievement over cultivating attitudes such as curiosity, respect for evidence, critical reflection, flexibility in thinking, and sensitivity to the environment. This study aimed to examine the effect of integrating the STEM approach with the Predict–Observe–Explain (POE) learning model, supported by the Web S.id platform, on senior high school students’ scientific attitudes when studying static fluids. The study employed a quantitative quasi-experimental method using a nonequivalent control group pretest–posttest design. The participants were 63 eleventh-grade students selected through purposive sampling and divided into an experimental group (32 students) and a control group (31 students). Students’ scientific attitudes were measured using a 12-item questionnaire with acceptable reliability (Cronbach’s alpha = 0.72). The data were analyzed for normality and homogeneity, and an independent-samples t-test and N-gain analysis were conducted. The results showed that the experimental group achieved greater improvement than the control group, with posttest means of 49.16 and 46.61, respectively, and a statistically significant difference between groups (p = 0.032). The effect size was moderate (Cohen’s d = 0.55). N-gain analysis further indicated that all measured indicators of scientific attitude improved more strongly in the experimental group, with the highest gain found in sensitivity in investigating the environment (g = 0.350). The novelty of this study lies in integrating STEM and POE through the Web S.id digital platform, while positioning scientific attitude as the primary outcome in physics learning, particularly in a simple water-dispenser project on static fluids. In conclusion, the STEM-integrated POE learning model supported by Web S.id was effective in fostering students’ scientific attitudes. This study contributes to physics education by providing an empirically supported instructional alternative that integrates project-based STEM learning, inquiry-oriented pedagogy, and digital media to strengthen affective outcomes alongside conceptual learning.